Customising clothes with embroidery : 15 fun projects to inspire you to upcycle the clothes you already own - Mabbott, Connie (Pen & Sword White Owl, 2021)
This collection of 15 projects shows how to add style to pre-owned or second-hand clothes using free-motion machine embroidery. Techniques shown include embroidered lettering, making applique patches, and embroidering directly onto the garment fabric.